Chemical etching and phase transformation of Nickel-Cobalt Prussian blue analogs for improved solar-driven water-splitting applications - Li, Yanbing; Jin, Zhiliang; Tsubaki, Noritatsu (Journal of Colloid and Interface Science, 2023)
[Display omitted] Although Prussian blue and its analogs (PB/PBAs) have open framework structures, large surface areas, uniform metal active sites, and tunable compositions, and have been investigated for a long time, owing to their unfavorable visible light responsiveness, they rarely been reported in photocatalysis. This largely limits their applications in solar-to-chemical energy conversion. Here, a continuous-evolution strategy was conducted to convert the poor-performance NiCo PBA (NCP) toward high-efficiency complex photocatalytic nanomaterials. First, chemical etching was performed to transform raw NCP (NCP-0) to hollow-structured NCP (including NCP-30, and NCP-60) with enhanced diffusion, penetration, mass transmission of reaction species, and accessible surface area. Then, the resultant hollow NCP-60 frameworks were further converted into advanced functional nanomaterials including CoO/3NiO, NiCoP nanoparticles, and CoNi2S4 nanorods with a considerably improved photocatalytic H2 evolution performance. The hollow-structured NCP-60 particles exhibit an enhanced H2 evolution rate (1.28 mol g-1h−1) compared with the raw NCP-0 (0.64 mol g-1h−1). Furthermore, the H2 evolution rate of the resulting NiCoP nanoparticles reached 16.6 mol g-1h−1, 25 times that of the NCP-0, without any cocatalysts.